(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Congenital adrenal hyperplasia (CAH) is a chromosomal disorder of sex development with frequency of approximately 1 per 15,000 new born and CAH is the most common cause masculinization at woman karyotype 46,XX. Patients with CAH need to be diagnosed and treated with hydrocortisone early, after birth. Late and non-continuous treatment with hydrocortisone causes complete masculinization, the patient develops like a man. Patients: All patients CAH have karyotype 46,XX with symptoms of complete masculinization were treated at Vietduc hospital from 2015 to 2023. Method: Describe the series of cases. Results: Five patients karyotype 46,XX, from 8 to 26 years old with male appearance and personality, four patients gave birth to male gender. Patients with clitoromegaly such as the penis, have poorly developed uterus and ovaries, primary amenorrhea, undeveloped of breasts, no testicles, they all choose male sex and accept operation elimination of uterus and ovaries. Conclusions: CAH was a catalyst for DSD at patients with karyotype 46,XX. Late trait with hydrocortisone at patients CAH gives rise to complete masculinization at 46,XX CAH patient, and those choosing to live with the male sex but infertility.